Intelligent Public Health Platform: A Multi-Stage Operational Process for Emergency Prevention and Health Management - Chen, Lanzhen; Lin, Rudan; Li, Xiaopeng; Ding, Xiaopan (International Journal of Electric Power and Energy Studies, 2025)
The deep integration of IoT technology and 5G communication is reshaping the public health emergency response system. This paper centers on the construction of an intelligent public health prevention and control platform, focusing on its operational process and expected results. The platform covers three stages: pre-hospital emergency response, in-hospital treatment and post-hospital rehabilitation. It constructs a multi-level collaborative intelligent medical system, integrating core modules such as 5G emergency vehicle dynamic dispatching, real-time transmission of multimodal vital signs, and intelligent allocation of regional resources. The platform realizes precise positioning of pre-hospital patients and ambulance path optimization, dynamic allocation of ICU and emergency beds within the hospital, and post-hospital remote health monitoring and personalized rehabilitation management. The platform not only supports highly effective response to public health emergencies, but also promotes the intelligence and refinement of medical processes by optimizing the allocation of medical resources and improving the level of health management.